Wave-induced variations in noctilucent cloud brightness: model and experimental studies. (July 2020) - Shevchuk, Nikita; Pertsev, Nikolay; Dalin, Peter; Perminov, Vladimir
Abstract: The paper describes a dynamical (geometrical) model of gravity-wave-induced noctilucent cloud (NLC) brightness. NLC brightness dependences on gravity wave parameters are presented. Results of the inverse-problem solution are addressed as well. It is shown that relative variations of NLC brightness are mainly dependent on the amplitude of a gravity wave, its horizontal wavelength and unperturbed thickness of an NLC layer. It is also shown that the model can be used for determining a geometric amplitude of a perturbing wave from a relative brightness distribution (inverse problem) and that the uncertainty of the geometric wave amplitude is mainly defined by an uncertainty of the cloud layer thickness. Highlights: Undulation of the top and bottom of a noctilucent cloud layer causes waves in its brightness field. This effect alone may account for main features of observing brightness field. Geometrical undulation amplitude can be estimated from a known brightness amplitude. Estimation uncertainty is determined mainly by an unknown width of a cloud layer.